Incels, autism, and hopelessness: affective incorporation of online interaction as a challenge for phenomenological psychopathology - Tirkkonen, Sanna K.; Vespermann, Daniel (Frontiers in psychology, 2023)
Recent research has drawn attention to the prevalence of self-reported autism within online communities of involuntary celibates (incels). These studies suggest that some individuals with autism may be particularly vulnerable to the impact of incel forums and the hopelessness they generate. However, a more precise description of the experiential connection between inceldom, self-reported autism, and hopelessness has remained unarticulated. Therefore, this article combines empirical studies on the incel community with phenomenological and embodiment approaches to autism, hopelessness, and online affectivity. We analyze three interrelated aspects of online interactions in incel communities - worldview, bodily self-relation, and mutual dismissals - and examine how these elements contribute to the consolidation of the loss of significant life possibilities. By investigating the potential negative influence of specific online environments on affective dispositions, our approach contributes to the debate on current challenges to "situate" phenomenological psychopathology.
Gesehen am 12.07.2024